The Mapping of Irrigated Paddy Fields which were Polluted by Detergent Waste in Kolam Village, Percut Sei Tuan Sub-district, Deli Serdang District - Mulkan Syahputra; supriadi; Marpaung, Purba (Jurnal Online Pertanian Tropik, 2021)
Rice is the staple food of the Indonesian people and in some places polluted by waste. This research aim was to provide a survey and map on the effects of detergent waste (phosphate available), electrical conductivity and soil pH in Kolam Village, Percut Sei Tuan Subdistrict of Deli Serdang District and analysis of sample points to P available, electrical conductivity and soil pH. This research started in September 2017 until January 2018. The method used was Grid Free and P available analysis used Bray II method, analysis of Electrical Conductivity with conductivity meter and analysis of soil pH with a pH meter. The results showed that the P available distribution consisted of very low (18%), low (52%) and moderate (30%). The distribution of soil electrical conductivity was low and the pH of the soil was acidic. Based on the analysis of sample points on P available, Electrical Conductivity and soil pH showed that the farther the distances from the irrigation pollutant channel, the availability of P decreased (0.088 ppm / meter) but did not affect the pH and electrical conductivity.